Cross indicator analysis between wind energy potential and urban morphology. (December 2017) - Wang, B.; Cot, L.D.; Adolphe, L.; Geoffroy, S.; Sun, S.
Abstract: Wind energy potential in built environment can be exploitable in a proper condition. With improvement of computer science, CFD simulation with complex building configuration or city models becomes accessible. This paper's main task is to analyse the relationship between urban wind energy potential and urban morphology through indicator studies in order to promote urban wind energy development. Six typical real urban forms in neighbourhood scale were selected from the primary wind potential evaluation with urban morphological character analysis. A set of morphological indicators that are potentially correlated with wind environment were defined. Wind energy potential over the roofs of the highest buildings in each urban tissue was evaluated. Simulation results show that the two wind energetic indicators, wind potential capacity M′ and wind potential density D′ vary with different urban tissues and different wind conditions. Through the correlation analysis, we found that several urban morphological indicators have significant correlation with the two wind potential indicators. With help of these morphological indicators, we can compare much accurately and easily the output of wind potential over roof of different urban tissues, before taking the time-consuming CFD simulation for many complex urban forms. Highlights: Potential windy urban forms were evaluated and selected. Potential urban morphological indicators having interaction with wind environment were selected. Wind energy potential over roof of six real urban tissues was evaluated and compared. Several urban morphological indicators were found with high correlation with wind energy indicators.